2023
DOI: 10.1038/s41598-023-29659-w
|View full text |Cite
|
Sign up to set email alerts
|

Graft rejection episodes after keratoplasty in Japanese eyes

Abstract: We aimed to investigate the clinical characteristics and risk factors for graft rejection after keratoplasty in Japanese patients. We enrolled 730 cases (566 patients) of penetrating keratoplasty (PK, N = 198), Descemet’s stripping automated endothelial keratoplasty (DSAEK, N = 277), non-Descemet’s stripping automated endothelial keratoplasty (nDSAEK, N = 138), and Descemet membrane endothelial keratoplasty (DMEK, N = 117). The incidence, clinical characteristics, and possible risk factors for graft rejection … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Corneal graft rejection was defined as new endothelial precipitates with or without corneal edema, anterior chamber inflammation, rejection line, corneal vascularization, and peripheral anterior synechia. 12,13 Primary graft failure was defined as the failure of corneal clearance within 3 months of surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Corneal graft rejection was defined as new endothelial precipitates with or without corneal edema, anterior chamber inflammation, rejection line, corneal vascularization, and peripheral anterior synechia. 12,13 Primary graft failure was defined as the failure of corneal clearance within 3 months of surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Corneal transplantation, or keratoplasty, represents a critical surgical intervention for restoring vision in individuals affected by corneal opacities, dystrophies, or scarring [9][10][11]. Despite the procedure's notable success rates, the postoperative period is fraught with the challenge of immune-mediated graft rejection, a significant cause of graft failure and subsequent vision loss [11]. The introduction of the COVID-19 vaccine has sparked a debate over its potential impact on the incidence or intensity of corneal transplant rejection [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have reported a modi ed version of the DSEK procedure known as non-Descemet stripping endothelial keratoplasty (nDSEK), where the procedure of stripping off the Descemet membrane is no longer required. Thus prior studies have demonstrated positive clinical outcomes for both nDSEK [1,2] and non-Descemet stripping endothelial keratoplasty in DSAEK [3].…”
mentioning
confidence: 99%